2021
DOI: 10.1259/bjrcr.20210075
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite crystal deposition disease around the hip: a rare cause of piriformis syndrome and ischiofemoral impingement

Abstract: Hydroxyapatite crystal deposition disease (HADD) around the hip is typically described involving the gluteal tendons. However, HADD can occur in any location and result in varied clinical presentations. Even with small deposits, symptoms can be significant and imaging findings may appear aggressive, mimicking infection and malignancy particularly when in an atypical location. We illustrate cases of both common and rare locations of HADD around the hip, in particular presenting as greater trochanteric pain syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Calcific tendinitis of the piriformis is scarce in medical literature with a recent review finding only two available cases reported [6]. A recent paper also reports a case of piriformis syndrome, diagnosed on MRI with findings of a calcific deposit with surrounding oedema within the proximal piriformis muscle adjacent to the sciatic nerve [7]. In this case, the patient gained significant symptoms improvement with steroid injection and low-energy shockwave therapy.…”
Section: Discussionmentioning
confidence: 92%
“…Calcific tendinitis of the piriformis is scarce in medical literature with a recent review finding only two available cases reported [6]. A recent paper also reports a case of piriformis syndrome, diagnosed on MRI with findings of a calcific deposit with surrounding oedema within the proximal piriformis muscle adjacent to the sciatic nerve [7]. In this case, the patient gained significant symptoms improvement with steroid injection and low-energy shockwave therapy.…”
Section: Discussionmentioning
confidence: 92%